2001
DOI: 10.1016/s1386-1425(01)00474-7
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy of lanthanide ions in ZnO–TeO2 glasses

Abstract: Zinc tellurite glasses of compositions 19ZnO-80TeO 2 -1Ln 2 O 3 with Ln= Eu, Er, Nd and Tm were prepared by melt quenching. The absorption spectra were measured and from the experimental oscillator strengths of the f f transitions the Judd-Ofelt parameters V u were obtained. The values of the V u parameters are in the range usually observed for oxide glasses. For Nd 3 + and Er 3 + , luminescence spectra in the near infrared were measured and the stimulated emission cross sections | p were evaluated for some la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(47 citation statements)
references
References 34 publications
10
36
0
1
Order By: Relevance
“…It was found that the building units of these glasses are TeO 4 , TeO 3+1 and TeO 3 groups. The four oxygens in the TeO 4 are located at four vertices of a trigonal bipyramid and TeO 3+1 groups are similar to TeO 4 but with a long Te-O bond while TeO 3 groups in which one of the Te sp3 hybrid orbitals is occupied by lne pair of electrons, where the oxygens are arranged at three vertices of a tetrahedron [4,11]. In addition, the glass formation in TeO 2 -ZnO binary system strongly depends on the cooling rate and the size of the melt, especially in the TeO 2 -rich region [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the building units of these glasses are TeO 4 , TeO 3+1 and TeO 3 groups. The four oxygens in the TeO 4 are located at four vertices of a trigonal bipyramid and TeO 3+1 groups are similar to TeO 4 but with a long Te-O bond while TeO 3 groups in which one of the Te sp3 hybrid orbitals is occupied by lne pair of electrons, where the oxygens are arranged at three vertices of a tetrahedron [4,11]. In addition, the glass formation in TeO 2 -ZnO binary system strongly depends on the cooling rate and the size of the melt, especially in the TeO 2 -rich region [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to form pure vitreous TeO 2 and it has been suggested [3] that this is due to the lone pair of electrons in one of the equatorial positions of the [TeO 4 ] polyhedron. The repulsive forces in this zone hinder the free movement of the polyhedra in space during the cooling of the melt.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescence quantum yield of ZnO:Er is, in general, less than 5% for the green and the red emissions. These values are short compared to that of the Er 3+ doped in similar bulk materials [33,34]. The lengthening of the decay and the increase of the estimated quantum yield in samples 5 and 6, compared with the rest samples, reveal that the luminescence quenching is less for the two, probably indicating that in these two samples more Er 3+ ions were doped into the internal area of ZnO, different from the rest samples where majority of Er 3+ ions were within the surface layer, if not all of them.…”
Section: Article In Pressmentioning
confidence: 82%